2015
DOI: 10.1038/srep08248
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome sequencing reveals that mutations in myosin-5 confer resistance to the fungicide phenamacril in Fusarium graminearum

Abstract: To determine the mechanism of resistance to the fungicide phenamacril (JS399-19) in Fusarium graminearum, the causal agent of Fusarium head blight, we sequenced and annotated the genome of the resistant strain YP-1 (generated by treating the F. graminearum reference strain PH-1 with phenamacril). Of 1.4 million total reads from an Illumina-based paired-end sequencing assay, 92.80% were aligned to the F. graminearum reference genome. Compared with strain PH-1, strain YP-1 contained 1,989 single-nucleotide polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
95
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(98 citation statements)
references
References 45 publications
0
95
0
Order By: Relevance
“…Fungicides containing phenamacril had the greatest effect, while 48% phenamacril · tebuconazole SC treatment (82.2%) was significantly more effective than phenamacril alone (66.7%). Phenamacril, a new fungicide classified as B6 (an phenylpyrrole fungicide selected from fludioxonil and fenpiclonil), has a new mode of action and is also considered environmentally safe, but its efficacy depends on the spray timing, concentration and method used . Studies of 48% phenamacril · tebuconazole SC application are therefore essential for enhancing its effectiveness.…”
Section: Resultsmentioning
confidence: 99%
“…Fungicides containing phenamacril had the greatest effect, while 48% phenamacril · tebuconazole SC treatment (82.2%) was significantly more effective than phenamacril alone (66.7%). Phenamacril, a new fungicide classified as B6 (an phenylpyrrole fungicide selected from fludioxonil and fenpiclonil), has a new mode of action and is also considered environmentally safe, but its efficacy depends on the spray timing, concentration and method used . Studies of 48% phenamacril · tebuconazole SC application are therefore essential for enhancing its effectiveness.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, we found that a point mutation S217 L or E420K in FgMyo1 is responsible for F. graminearum resistance to phenamacril . In addition, another 11 amino acid substitutions also confer resistance to phenamacril . Upregulation of drug target genes is another way to acquire resistance or tolerance to antifungal agents.…”
Section: Discussionmentioning
confidence: 99%
“…These include point mutation of FgMyo1 and up‐regulated FgMYO1 expression by FgTfmI. Mutations in the FgMyo1 resulted in high resistance to phenamacril, and were obtain with a high frequency in the laboratory screening with a high concentration of phenamacril . However, the deletion mutant ΔFgTfmI showed hypersensitivity to phenamacril (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Benzimidazole fungicides bind to β‐tubulin to inhibit mycelial growth of plant pathogenic fungi, and the resistance mechanism is the point mutation of amino acids encoding the β‐tubulin in Botrytis cinerea and Sclerotinia sclerotiorum (Liu et al, , ; Zhu, Zhou, Li, Zhu, & Ma, ), or amino acids encoding the β 2 ‐tubulin gene in F. graminearum (Liu, Duan, Ge, Chen, & Zhou, ; Liu et al, ). The active target of the cyanoacrylate fungicide phenamacril is myosin 5 of the FGSC, and the point mutation in its coding gene leads to resistance of the FGSC to phenamacril (Hou et al, ; Li et al, ; Zheng et al, ). Therefore, there was no cross‐resistance between metconazole and carbendazim or phenamacril in F. graminearum , and positive cross‐resistance relationship between metconazole and epoxiconazole, difenoconazole or tebuconazole in F. graminearum .…”
Section: Discussionmentioning
confidence: 99%